Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Konsumen Depot Air Minum Semuril Marelan - Nuranisa Fitri; Kamilah Kamilah; Tri Inda Fadhila Rahma (PENERBIT LAFADZ JAYA, 2022)
This study aims to determine the effect of price, income and service quality on consumer demand for Semuril drinking water depot. The sample of this research is the consumers of Semuril drinking water depot, with a total sample of 100 people who were selected using simple random sampling. The analytical method used in this research is a quantitative method with multiple linear regression analysis. The results showed that: (1) price has a significant effect on consumer demand; (2) income does not have a significant effect on consumer demand; and (3) service quality has a significant effect on consumer demand.